A study of job performance in private sector in Malaysia: a field study / Mohd Faizal Abdul Aziz - Abdul Aziz, Mohd Faizal (Faculty of Business and Management, 2010)
As a MNCs company, customers are the most importance key in the Lafarge Concrete (M) Sdn Bhd as the business nature. The performance of employees will be ensured the business growth and the strengths to compete with other rivals in the market.Based on this believe, this study was conducted which is to know whether Lafarge Concrete (M) Sdn Bhd is fulfilling the customer needs in their life. For the Chapter 1 explaining the background of study, Chapter 2 explains the literature review and theoretical framework, Chapter 3 focus to research methodology and Chapter 4 will followed by finding and lastly conclusion and recommendation. The finding shows the factors that contribute to the study of job performance in private sector in Malaysia company need to take an action to overcome the problems.